2011
DOI: 10.1007/s10120-011-0048-y
|View full text |Cite
|
Sign up to set email alerts
|

Value of sentinel lymph node mapping using a blue dye-only method in gastric cancer: a single-center experience from North-East Hungary

Abstract: Background Forty percent of patients with gastric cancer have unnecessarily extended lymph node dissections with higher rates of morbidity and mortality than those in nonextended procedures. Successful sentinel lymph node (SLN) mapping may help to reduce the number of extended lymphadenectomies. Methods SLN mapping was investigated by a blue dyeonly method in patients with gastric cancer. The first cohort of patients (n = 16) were marked submucosally by an endoscopist and in the second cohort of patients (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 23 publications
(26 reference statements)
2
31
0
Order By: Relevance
“…Sampling of station 10 and compartment 3 nodes (13-16) was optional if macroscopically suspicious, so we did not routinely calculate the values of these stations. Our SLN marking method and the histological examination were described earlier [12]. The position of lymph nodes was labelled according to the Japanese classification of gastric carcinoma (JCGC) [13].…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling of station 10 and compartment 3 nodes (13-16) was optional if macroscopically suspicious, so we did not routinely calculate the values of these stations. Our SLN marking method and the histological examination were described earlier [12]. The position of lymph nodes was labelled according to the Japanese classification of gastric carcinoma (JCGC) [13].…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…Studies from Japan and from Western Europe have demonstrated a high detection rate (93.7 %) and an accuracy of 92 % for SLN biopsy in patients with gastric cancer [11]. We have evaluated, for the first time in Hungary, the validity of SLN mapping using a blue dye-only method in gastric cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, preoperative diagnostic tools have a low sensitivity and specificity for defining these patient subpopulations. Sensitivity, specificity and accuracy of spiral computer tomography for detection of pathologic LN involvement are 73.1%, 50.0% and 84.2%, respec tively [11,12] . Endoscopic ultrasonography has an accuracy of 68.6%, with a sensitivity and specificity of 66.7% and 73.7%, respectively [11,13] .…”
Section: Ln Involvementmentioning
confidence: 99%
“…Sensitivity, specificity and accuracy of spiral computer tomography for detection of pathologic LN involvement are 73.1%, 50.0% and 84.2%, respec tively [11,12] . Endoscopic ultrasonography has an accuracy of 68.6%, with a sensitivity and specificity of 66.7% and 73.7%, respectively [11,13] . The real problem of these imaging procedures is that exclusion of endoscopic ultrasonography, only the size of the LNs is taken into account.…”
Section: Ln Involvementmentioning
confidence: 99%
See 1 more Smart Citation